Food and feeding habits of the mahseer, Tor putitora (Hamilton - Gupta, M Das (Indian Journal of Fisheries, 2011)
Though some work on the food and feeding habits of Tor putitora has been done elsewhere (Sehgal et al. 1971, Das and Pathani 1978 and Nautiyal and Lai 1984) but so far there is no report on this aspect from the North-Eastern India. The present study was, therefore, undertaken.